Моделювання роботи теплообмінних апаратів систем енерго- та теплопостачання високотемпературних технологічних установок - Кошельнік, Олександр Вадимович; Хавін, Євген Валерійович; Павлова, Вікторія Геннадіївна (НТУ "ХПІ", 2015)
Представлена математическая модель тепловых процессов в регенеративных теплообменных аппаратах с неподвижной огнеупорной насадкой, используемых для подогрева воздуха горения в высокотемпературных теплотехнологических агрегатах. На eё основе создана программа, моделирующая работу воздухонагревателей доменных печей с учетом технологических и эксплуатационных ограничений. Это позволяет получить значения температур теплоносителей и насадки во времени и по высоте теплообменника. Полученные данные могут быть использованы для выбора конструктивных и режимных параметров регенераторов как при реконструкции действующих, так и при проектировании новых высокотемпературных теплотехнологических агрегатов комплексов.

The mathematical model of the heating processes in the regenerative heat exchangers with stationary refractory checker-work used for the combustion air pre-heat in the high-temperature heat engineering installations is presented. On this base the procedure simulating the hot-air stoves operation with allowance for technological and operational limitations is created. This makes possible to determine the heat transfer agents and checker-work temperatures in time intervals and in heat exchanger height. The data obtained can be applied for selection of the regenerators’ structural and processing properties during the reconstruction of the operating units as long as in designing of the modern high-temperature heat engineering equipment.
Simulation of heat exchange units operation of power- and heat supply systems in high-temperature engineering installations
Keywords: ВТУ; закон Фур'є; закон Н’ютона-Ріхмана; тепловий баланс; регенеративні теплообмінники; промисловість; математичне моделювання